Reforming Polri’s community policing: A procedural justice and human resource approach to building police legitimacy - Fitrianto, Arief; Suhariadi, Fendy; Minarno, Nur Basuki (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the challenges of implementing community policing (Polmas) in Indonesia by integrating Procedural Justice Theory and Human Resource Theory. It focuses on how the competencies, leadership, and incentive systems within the Indonesian National Police (Polri) foster police legitimacy and public trust. A literature review was conducted by analyzing peer-reviewed articles from reputable databases such as Scopus and Web of Science. Thematic analysis was employed to identify patterns, research gaps, and opportunities to strengthen community policing practices in Indonesia, particularly within the organizational structure of Polri. The study reveals that procedural justice remains underutilized within Polri, which relies on repressive approaches. Human resource factors, including inadequate training, hierarchical leadership, and ineffective incentive structures, hinder the success of community policing. Additionally, police legitimacy requires a holistic strategy that integrates procedural fairness, distributive justice, lawfulness, and service effectiveness to rebuild public trust. This research contributes to the limited knowledge of community policing in developing countries by linking Procedural Justice Theory and Human Resource Theory within the context of Polri. It provides practical insights for policymakers by recommending reforms in police training, performance evaluations, and community engagement strategies to establish sustainable, trust-based policing models in Indonesia.